2004
DOI: 10.1099/mic.0.26867-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a topoisomerase IV in actinobacteria: purification and characterization of ParYR and GyrBR from the coumermycin A1 producer Streptomyces rishiriensis DSM 40489

Abstract: The biosynthetic gene clusters of the gyrase inhibitors coumermycin A 1 and clorobiocin contain two different resistance genes (gyrB R and parY R ). Both genes code for B subunits of type II topoisomerases. The authors have now overexpressed and purified the encoded proteins, as well as the corresponding A subunits GyrA and ParX. Expression was carried out in Streptomyces lividans in the form of hexahistidine fusion proteins, allowing purification by nickel affinity chromatography. The complex of GyrA and GyrB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Sequence analysis of the biosynthetic gene cluster of simocyclinone revealed that it contains several genes with high degrees of similarity to those involved in the biosynthesis of the coumarin moieties of novobiocin, clorobiocin, and coumermycin (13,39). However, the simocyclinone gene cluster does not contain an obvious resistance gene that would give a clue as to its target (13,39); this is in contrast to the biosynthetic gene clusters of novobiocin, clorobiocin, and coumermycin, all of which contain genes encoding aminocoumarin-resistant topoisomerase subunits (35,36). Simocyclinone D8 has been shown to exhibit antibiotic activity against gram-positive bacteria, as well as cytostatic effects against human tumor cell lines; little or no activity has been found against gram-negative organisms such as E. coli (32,33).…”
mentioning
confidence: 52%
“…Sequence analysis of the biosynthetic gene cluster of simocyclinone revealed that it contains several genes with high degrees of similarity to those involved in the biosynthesis of the coumarin moieties of novobiocin, clorobiocin, and coumermycin (13,39). However, the simocyclinone gene cluster does not contain an obvious resistance gene that would give a clue as to its target (13,39); this is in contrast to the biosynthetic gene clusters of novobiocin, clorobiocin, and coumermycin, all of which contain genes encoding aminocoumarin-resistant topoisomerase subunits (35,36). Simocyclinone D8 has been shown to exhibit antibiotic activity against gram-positive bacteria, as well as cytostatic effects against human tumor cell lines; little or no activity has been found against gram-negative organisms such as E. coli (32,33).…”
mentioning
confidence: 52%
“…Apparently, this antibiotic has evolved for optimal interaction with its targets, gyrase and topo IV. In this context, it is noteworthy that the clorobiocin gene cluster contains two resistance genes protecting the natural clorobiocin producer Streptomyces roseochromogenes from the toxic effect of the antibiotic: gyrB R , which encodes an aminocoumarin-resistant gyrase subunit, and parY R , which encodes an aminocoumarin-resistant topo IV subunit (20). In contrast, the novobiocin biosynthetic gene cluster contains only a gyrB R resistance gene (21,22).…”
Section: Resultsmentioning
confidence: 99%
“…Streptomycetes, however, have no xerCD-like genes (6, 23), though they do have a topoisomerase IV biochemically able to catalyze ATP-dependent decatenation (6,23,38). Whether this enzyme plays a role in chromosome decatenation during sporulation and/or interacts with FtsK SC is yet to be revealed.…”
Section: Discussionmentioning
confidence: 99%